Asymptotics in dynamics, geometry and PDEs; generalized borel summation vol. I - Costin, O. 1960- (Ovidiu) (Publications of the scuola normale superiore, CRM series, 2011)
These are the proceedings of a one-week international conference centered on asymptotic analysis and its applications. They contain major contributions dealing with mathematical physics: PT symmetry, perturbative quantum field theory, WKB analysis; local dynamics: parabolic systems, small denominator questions; new aspects in mould calculus, with related combinatorial Hopf algebras and application to multizeta values; a new family of resurgent functions related to knot theory.